A critical look at Chinese 'debt-trap diplomacy': the rise of a meme. Issue 1 (2nd January 2020) - Brautigam, Deborah
ABSTRACT: In 2017, a meme was born in a think tank in northern India: Chinese 'debt-trap diplomacy'. This meme quickly spread through the media, intelligence circles and Western governments. Within 12 months it generated nearly 2 million search results on Google in 0.52 seconds and was beginning to solidify into a deep historical truth. Stories can contain truths and falsehoods. Human emotions, including negativity bias, prime us to think in certain ways. This paper retells a series of stories about China's international involvement, including in Angola, Djibouti, Sri Lanka and Venezuela, that challenge the media's spin. It concludes with some suggestions about the relationship between academia and the media and policy worlds, and the need for scholars to speak 'truth' to 'power'.